Design of microchannel Fischer–Tropsch reactor using cell-coupling method: Effect of flow configurations and distribution. (2nd April 2016) - Park, Seongho; Jung, Ikhwan; Lee, Yongkyu; Kshetrimayum, Krishnadash S.; Na, Jonggeol; Park, Seongeon; Shin, Seolin; Ha, Daegeun; Lee, Yeongbeom; Chung, Jongtae; Lee, Chul-Jin; Han, Chonghun
Abstract: The objective of this study is to design a microchannel Fischer–Tropsch reactor with the evaluation of several flow configurations and distribution effect. A cell coupling computation was carried out for the microchannel reactor of five different flow configurations. In the cell coupling method, all the process and cooling channels are decomposed into a number of unit cells, and then coupled to solve the material and energy balances. The realistic flow distribution effect was incorporated into the model by using results obtained from computational fluid dynamics (CFD). The kinetic model was validated with experimental data, and the results of the reactor model was compared with data taken from the literature and the results were found to be in good agreement. Several case studies were conducted to see the effect of flow configurations, flow distribution, and catalyst loading zones. It was observed that the geometry of cross-co-cross current was found to give the best performance among the designs considered. The study also reveals that flow distribution and catalyst loading zone need to be carefully controlled for the safe, robust, and reliable reactor design and operation. Highlights: We build a 3D model for the large scale microchannel FT reactor. The model was validated over the various operating conditions. Five different flow configurations were modeled by cell-coupling approach. Flow distribution effect was incorporated into the model. Proper catalyst loading strategy for the safe heat removal was proposed.